The Effect of Flexible Work System, Workload, Work Ability, Job Satisfaction, Employee Engagement and Work Stress On Employee Performance (Case Study at PT Mecoindo) - Tuti Irawati Suparman (Jurnal Indonesia Sosial Teknologi, 2024)
This study examines the effect of flexible work systems, workload, work ability, job satisfaction, employee engagement, and job stress on employee performance. The goal is to gain a comprehensive understanding of how these factors interrelate and affect overall employee performance within the organization. This study uses a quantitative survey method approach to collect data from a sample of employees at PT Mecoindo. Quantitative analysis involves statistical techniques such as regression analysis and correlation analysis to explore the relationship between the independent variable (flexible work system, workload, work ability, job satisfaction, employee engagement, and job stress) and the dependent variable (employee performance). The findings show that flexible work systems positively affect employee performance. In addition, workloads at moderate levels can improve employee performance. Job satisfaction was identified as a significant predictor of employee performance. Employee engagement also emerged as a key factor. On the other hand, high levels of job stress were found to negatively impact employee performance, underscoring the importance of managing stress levels in the workplace.